2011
DOI: 10.7732/kjpr.2011.24.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Supplementation with Extracts from the Marine Brown Alga Eisenia bicyclis on Macrophages

Abstract: -A large number of edible seaweeds are consumed by the coastal peoples of Asia. Some of them are used in traditional remedies in many parts of the world. In this study we investigated effects of supplementation with ethyl acetate extracts of the brown alga Eisenia bicyclis (EBE) on rat macrophage to evaluate the possibilities as immune-modulators. Twelve male SD rats were divided into two groups and the treatments were as follows: A, no Eisenia bicyclis extract (EBE) intake and distilled water ; B, oral supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The challenge of experimental animals or isolated cells with lipopolysaccharide (LPS) is a common model of acute inflammation, mimicking the response to bacterial infection. A 5-week treatment of rats with Eisenia (= Ecklonia ) bicyclis extract mediated a reduced inflammatory activation of peritoneal macrophages upon in vitro LPS stimulation through inhibition of NF-κB activity [ 21 ]. This was associated with reduced iNOS expression and nitric oxide (NO) production.…”
Section: Whole Seaweed or Crude Extract Supplementationmentioning
confidence: 99%
“…The challenge of experimental animals or isolated cells with lipopolysaccharide (LPS) is a common model of acute inflammation, mimicking the response to bacterial infection. A 5-week treatment of rats with Eisenia (= Ecklonia ) bicyclis extract mediated a reduced inflammatory activation of peritoneal macrophages upon in vitro LPS stimulation through inhibition of NF-κB activity [ 21 ]. This was associated with reduced iNOS expression and nitric oxide (NO) production.…”
Section: Whole Seaweed or Crude Extract Supplementationmentioning
confidence: 99%
“…Los resultados coinciden con los encontrados por Jiang et al (2013) quienes trabajaron con polisacáridos sulfatados de Ascophyllum nodosum y demostraron la producción de especies reactivas de oxígeno en células RAW 264.7. La inhibición en la producción de anión superóxido implica una fuerte actividad antioxidante de los fucoidanos sobre ROS (So et al 2007), en ese sentido otros autores han demostrado que empleando el extracto de Eisenia bicyclis y nanopartículas constituidas por quitosano y FFv se inhibe la producción de anión superóxido y la actividad fagocítica en macrófagos aislados de ratas y células RAW 264.7 respectivamente (Namkoong et al 2011, Huang & Li 2014.…”
Section: Figuraunclassified
“…They also contain the storage polysaccharide laminarin, alginate, fucoxanthin and fucoidan with immunological activities (Joe et al, 2006). It has been also known that brown algae extracts closely linked to its protective properties against free radical attack and have anti-oxidant, immunomodulatory effects (Hu et al, 2010;Kang et al, 2004;Namkoong et al, 2011) and numerous studies have shown that fucoxanthin has considerable potential and promising applications in human health (Peng Fig. 1.…”
Section: Introductionmentioning
confidence: 99%